Inosine monophosphate and inosine differentially regulate endotoxemia and bacterial sepsis. Issue 11 (30th September 2021) - Lovászi, Marianna; Németh, Zoltán H.; Gause, William C.; Beesley, Jennet; Pacher, Pál; Haskó, György
Abstract: Inosine monophosphate (IMP) is the intracellular precursor for both adenosine monophosphate and guanosine monophosphate and thus plays a central role in intracellular purine metabolism. IMP can also serve as an extracellular signaling molecule, and can regulate diverse processes such as taste sensation, neutrophil function, and ischemia‐reperfusion injury. How IMP regulates inflammation induced by bacterial products or bacteria is unknown. In this study, we demonstrate that IMP suppressed tumor necrosis factor (TNF)‐α production and augmented IL‐10 production in endotoxemic mice. IMP exerted its effects through metabolism to inosine, as IMP only suppressed TNF‐α following its CD73‐mediated degradation to inosine in lipopolysaccharide‐activated macrophages. Studies with gene targeted mice and pharmacological antagonism indicated that A2A, A2B, and A3 adenosine receptors are not required for the inosine suppression of TNF‐α production. The inosine suppression of TNF‐α production did not require its metabolism to hypoxanthine through purine nucleoside phosphorylase or its uptake into cells through concentrative nucleoside transporters indicating a role for alternative metabolic/uptake pathways. Inosine augmented IL‐β production by macrophages in which inflammasome was activated by lipopolysaccharide and ATP. In contrast to its effects in endotoxemia, IMP failed to affect the inflammatory response to abdominal sepsis and pneumonia. We conclude that extracellular IMP and inosine differentially regulate the inflammatory response.